Transformation of Activities and Space in Malay Kampong as Heritage Kampong in Semarang City - Kurniati, Rina; Ristianti, Novia Sari; Dewi, Santy Paulla; Prihestiwi, Rosa Calista (Universitas Negeri Semarang, 2020)
Abstract. Urban development is a very dynamic process which determines by the function and the value of an area. Development of the city and the modernization causes social, economic and environmental changes and causes spatial transformation in the urban kampoong. The spatial transformation cannot be generalized and have different forms. Kampung Melayu is one of the kampung kota in the Semarang city that still survives till now. The function of Kampung Melayu is very vital and has enormous value in the colonial era so that it becomes a special attraction in the service trade sector. However, in the 20th century Kampung Melayu changed its function which led to changes in spatial planning in the region. Based on the results of the analysis, there are indications of decreased activity in the region regarding economic, environmental and social aspects both in the context of physical and non-physical changes. Thus, the purpose of this research is to make a spatial transformation that occurs in Kampung Melayu Semarang. The method used is a qualitative method. This study discusses the historical role of Malay villages from the future, how to assess the character of space and activities in Kampung Melayu and the spatial transformation in Kampung Melayu. The output of this research is spatial transformation that occurs in Kampung Melayu, Semarang CityKeywords: Spatial Transformation, Urban Kampoong, Kampoong Heritage.